2003
DOI: 10.17221/4153-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different organic amendment on winter wheat yields under long-term continuous cropping

Abstract: The observations were conducted on chernozem soil in a sugar-beet production region in . Six variants of organic amendment were examined: l -straw harvest, 2 -straw harvest + green manuring, 3 -straw incorporation, 4 -straw incorporation + green manuring, 5 -straw burning, 6 -straw burning till 1977 + intercrop, incorporation of farmyard manure at 10 t/ha since 1978. The effect of organic amendment on winter wheat continuous cropping was statistically significant. On average of the whole period (32 years), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 8 publications
1
14
0
2
Order By: Relevance
“…They also provide useful amounts of organic matter, as well as non-leguminous crops which, nevertheless, cannot fix atmospheric N 2 (Davies and Lennartsson, 2005). During 32 years of winter wheat cropping, Procházková et al (2003) found higher average yields with green manuring compared with straw incorporation into the soil, probably due to a slower decomposition and following release of nutrients by the latter.…”
Section: Soil Management Strategies For a Sustainable Agriculturementioning
confidence: 98%
“…They also provide useful amounts of organic matter, as well as non-leguminous crops which, nevertheless, cannot fix atmospheric N 2 (Davies and Lennartsson, 2005). During 32 years of winter wheat cropping, Procházková et al (2003) found higher average yields with green manuring compared with straw incorporation into the soil, probably due to a slower decomposition and following release of nutrients by the latter.…”
Section: Soil Management Strategies For a Sustainable Agriculturementioning
confidence: 98%
“…Nevertheless, many agricultural companies have no animal production or have significantly decreased production of farmyard fertilizers. Organic fertilization then may be replaced with straw left in the field after the harvest of cereals, although the effect of straw application on yield reported in literature is rather low (Powlson et al 1985, Thomsen and Jensen 1994, Procházková et al 2003). Yet, a positive influence of straw on soil properties was observed (Christensen 1986, Powlson et al 1987, Ocio et al 1991, Černý et al 2003).…”
mentioning
confidence: 99%
“…Rothrock and Cunfer (1986) and Maas and Kotze (1990) showed that the number and kind of microorganisms antagonistic against Gaeumannomyces graminis changed under the influence of different plants in crop rotation. Procházková et al (2003) found that wheat yield was not significantly affected by continuous cropping and the high production ability of wheat in the long-term experiment showed a high antiphytopathogenic potential of the soil under study.…”
mentioning
confidence: 82%